The influence of fatigue, ligament laxity and hormonal fluctuation on plantar pressure in female athletes - Silke, K. T.; Wunderlich, R. E.; Cebulski, S. F. (ESM 2010 emed scientific meeting, 2010)
Overuse injuries of the lower extremity compose over 20% of injuries in collegiate athletes, up to 50% of injuries in pediatric athletics (Arendt, 2003, Bennell, et al., 1996, Dalton, 1992) and a considerable portion of injuries in military recruits (Milgrom, et al., 1985, Rauh, et al., 2006). Like some traumatic injuries (acl tears) overuse/stress injuries are significantly more frequently observed in women (Taunton, et al., 2002). The etiology of sex differences in overuse injuries has been associated with various factors including training, anatomical differences, hormonal differences, and joint laxity. Joint laxity has also been associated with fluctuating hormone levels. Specifically, estrogen has been associated with suppression of collagen synthesis and decreased ligament cross-sectional area (Abubaker, et al., 1996, Booth, et al., 1970, Liu, et al., 1997, Samuel, et al., 1996). As collagen serves to provide stiffness to biological tissues such as ligaments and tendons, its breakdown can play a key role in enhanced joint laxity. In this study we quantify hormone levels, ligament laxity, and plantar pressure distribution to investigate the extent to which hormone fluctuation and fatigue interact to influence plantar pressure distribution and lower limb load.